In vitro/vivo antifungal activity study of novel mandelic acid derivatives as potential fungicides against Thanatephorus cucumeris - Huabin Shi; Longju Li; Dandan Song; Ya Zheng; Zhibing Wu (Arabian Journal of Chemistry, 2023)
To discover highly efficient and novel lead compounds against Thanatephorus cucumeris, a series of novel mandelic acid derivatives containing 1,3,4-thiadiazole thioether was designed and synthesized. The bioassay results revealed that target compound F10 exhibited excellent antifungal activity against T. cucumeris with EC50 value of 9.7 μg/mL. Further studies found that F10 not only significantly inhibited the growth of T. cucumeris mycelia but also effectively inhibited the formation of sclerotia, and exhibited significant in vivo protective (61.1%) and curative (67.9%) activities at 200 μg/mL. Mechanism studies demonstrated that F10 can damage the integrity of the cell membrane structure, resulting in increased permeability of the cell membrane, releasing the intracellular electrolyte and inhibiting the growth of fungi. In general, this work is helpful for managing the formation and diffusion of the infection source and provides an effective method to control rice sheath blight disease infected with sclerotia of T. cucumeris.